2012
DOI: 10.1037/a0026958
|View full text |Cite
|
Sign up to set email alerts
|

Gist-based conceptual processing of pictures remains intact in patients with amnestic mild cognitive impairment.

Abstract: Objective The picture superiority effect, better memory for pictures compared to words, has been found in young adults, healthy older adults, and, most recently, in patients with Alzheimer’s disease and mild cognitive impairment. Although the picture superiority effect is widely found, there is still debate over what drives this effect. One main question is whether it is enhanced perceptual or conceptual information that leads to the advantage for pictures over words. In this experiment, we examined the pictur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
1
22
0
4
Order By: Relevance
“…On the other hand, other results of the present study, e.g. the results which refer to a ‘picture superiority effect', were in parallel with previous research [48,49]. …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, other results of the present study, e.g. the results which refer to a ‘picture superiority effect', were in parallel with previous research [48,49]. …”
Section: Discussionsupporting
confidence: 81%
“…The lack of an enhancement effect for the recall of words in AD may suggest a ‘picture superiority effect'. In other words, a pictorial stimulus may be dual-coded (picture generates both verbal and image codes) or may be more salient because of its perceptual distinctiveness [48,49]. However, as a limitation we did not examine the arousal levels in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Gist memory encourages individuals to capture meaning, or remember the essential meaning, the "substance" of information, rather than exact words, numbers, or pictures. A recent experimental study showed that gist-based conceptual processing of pictures was preserved in persons with MCI, supporting the persons to extract and use gist information [20]. Therefore, [20].…”
Section: Resultsmentioning
confidence: 99%
“…A recent experimental study showed that gist-based conceptual processing of pictures was preserved in persons with MCI, supporting the persons to extract and use gist information [20]. Therefore, [20].…”
Section: Resultsmentioning
confidence: 99%
“…Recent reviews have yielded evidence supporting the existence of noun naming deficits in individuals with MCI [10,14]. However, individual studies have revealed contradictory results: while some studies suggest that individuals with MCI performed significantly more poorly on the BNT than HE subjects [4,5,6,7,8,9,11,12,13], other studies did not find significant differences between the two groups [10,25,26,27,28,29,30,31,32]. These inconsistent reports about the performance on BNT in MCI can be explained by differences in the diagnostic criteria, procedural differences in the naming tasks, and the possibility that only a segment of patients with MCI has naming deficits [33].…”
Section: Introductionmentioning
confidence: 93%